HUBUNGAN KETAHANAN DIRI DENGAN PERILAKU KESEHATAN REPRODUKSI PADA REMAJA DI SMA NEGERI 107 JAKARTA - Zahrah Rasyida Rasa Fathuhaq (2022)
Adolescents are at risk for behavioral problems, especially health problems caused by a lack of strong self-control both from within and from within. When teenagers are unable to cope with unfavorable situations, a risky behavior emerges: dangerous sex. This study aims to determine the relationship between self-defense and reproductive health in adolescents at SMA Negeri 107 Jakarta. The study used the Chi-Square test with a descriptive analytic approach with a cross sectional approach, a sample of 187 adult respondents and the sampling was done using cluster sampling technique. Data were collected using the Child & Youth Resilience Measure Received (CYRM-R) and Adolescent Reproductive Health (ARH) questionnaires. Both of these questionnaires have been tested for validity and reliability. Obtained p value 0.000 0.05 with OR = 7.558. The results showed that there was a relationship between self-control and reproductive health behavior in adolescents at SMA Negeri 107 Jakarta. Can Key that resilience is an important factor in behavior in reproductive health. Therefore, it is important to minimize adverse factors in individual resilience.